(3TYH GdGjeGfs - (3YHO GdLdjd Hf ehSi Hf YHO GdLdjd GdCfUGQj GdChSj GdbQWHj CHh eMeO GdbUQj,J (B608 (3g` s ((3YHO Gddg Hf eMeO Hf jMji Hf jhSa Hf eMeO GdChRGYi s)
(3ChdgG (B:s
(3GdTYHI GdChdi TgGOI Cf dG Edg EdG Gddg GdTYHI GdKGfjI GdEbQGQ HCf eMeO QShd Gddg GdTYHI GdKGdKI GdZSd ef GdLfGHI s
(3BNQgG (B:s
(3hLejY CfhGY YbGHI ai GdOfjG hGdBNQI hCf jHdZ HfG hHce HaVdg hdG jcdfG Edi (B( (3CfaSfG (B) (3hGZaQ di hdcd ef fXQ ai cJGHfG gPG ced cJGH TYH GdGjeGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B276 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B83s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B49s
Keywords: (3GdJUha hGdBOGH GdTQYjIs